Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jpm11111199
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis Identifies Precision Treatment with Paclitaxel for Hepatocellular Carcinoma Patients Harboring Mutant TP53 or Wild-Type CTNNB1 Gene

Abstract: Hepatocellular carcinoma (HCC) is an aggressive and chemoresistant cancer type. The development of novel therapeutic strategies is still urgently needed. Personalized or precision medicine is a new trend in cancer therapy, which treats cancer patients with specific genetic alterations. In this study, a gene signature was identified from the transcriptome of HCC patients, which was correlated with the patients’ poorer prognoses. This gene signature is functionally related to mitotic cell cycle regulation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…By identifying a gene signature from the transcriptome of HCC patients functionally related to mitotic cell cycle regulation, Lin et al demonstrated the sensitivity of HCC lines with mutant TP53 or wild-type CTNNB1 genes to taxanes using gene-drug association analysis. As a result, the study suggested a benefit of treatment with paclitaxel in this patient population [68]. A poor prognosis-associated signature was identified by Yang et al in patients with the TP53 mutation; subsequently, in silico screening of three targets (CANT1, CBFB, and PKM) and two agents (irinotecan and YM-155) were noted to have a potential therapeutic impact on patients with a poor prognosis-associated signature [69].…”
Section: Pt53mentioning
confidence: 79%
“…By identifying a gene signature from the transcriptome of HCC patients functionally related to mitotic cell cycle regulation, Lin et al demonstrated the sensitivity of HCC lines with mutant TP53 or wild-type CTNNB1 genes to taxanes using gene-drug association analysis. As a result, the study suggested a benefit of treatment with paclitaxel in this patient population [68]. A poor prognosis-associated signature was identified by Yang et al in patients with the TP53 mutation; subsequently, in silico screening of three targets (CANT1, CBFB, and PKM) and two agents (irinotecan and YM-155) were noted to have a potential therapeutic impact on patients with a poor prognosis-associated signature [69].…”
Section: Pt53mentioning
confidence: 79%
“…HCC is one of the most common malignant tumors in the world, and with the continuous development of medical technology and research on the molecular biology of tumors, targeted therapy for hepatocellular carcinoma is developing rapidly [1,2]. TERT, MLL4, CCNE1, TP53, and CTNNB1 were identified as commonly mutated genes in HCC [26][27][28][29][30]. Despite the availability of many potential therapeutic targets, the incidence and mortality rates of patients with HCC are still increasing currently [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of glutamine metabolism improves sorafenib Chemosensitization in oxoglutarate dehydrogenase-like (OGDHL)-defcient hepatoma cells [66]. Decreased glutamine synthesis results in growth inhibition of CTNNB1-mutated HCC xenografts by a combination of glutamine synthetase inhibitors and asparaginase inhibitors [67,68].…”
Section: Amino Acid Based Metabolic Biomarkersmentioning
confidence: 99%